Increased serum C-reactive protein levels are associated with shorter survival and development of second cancers in chronic lymphocytic leukemia. (2nd January 2017) - Herishanu, Yair; Polliack, Aaron; Shenhar-Tsarfaty, Shani; Weinberger, Ronit; Gelman, Ram; Ziv-Baran, Tomer; Zeltser, David; Shapira, Itzhak; Berliner, Sholomo; Rogowski, Ori
Abstract: Background: Chronic lymphocytic leukemia (CLL) is characterized by a heterogeneous clinical course, ranging from stable to more aggressive disease. Herein, we determined the prognostic significance of serum C-reactive protein (CRP) levels in patients with CLL Methods: A retrospective cohort study reviewing the records of 107 consecutive treatment naïve patients with CLL and a control group comprised of apparently healthy individuals attending for periodic health examinations. Results: The median CRP level of patients with CLL was 0.19 mg/dL (0–2.9). In univariate analysis, high-CRP levels (≥0.4 mg/dL) were significantly associated with an increased risk of mortality (HR = 3.97, 95%CI 1.64–9.62, p = .002) and development of second solid cancers (HR = 4.54, 95%CI 1.57–13.11, p = .005), compared to low-CRP values (<0.4 mg/dL). In multivariate analysis, high-CRP retained statistical significance for all-cause mortality (HR = 2.81, 95%CI 1.04–7.57, p = .04) and the development of second solid malignancies (HR = 4.54, 95%CI 1.57–13.11, p = .005). Moreover, when compared to an apparently healthy population, CLL patients with high CRP levels had more than an eightfold risk of cancer. Conclusions: Elevated baseline CRP levels are associated with shorter survival and development of second cancers in patients with CLL. We suggest that increased CRP in patients with CLL may justify a more rigorous search for second cancers. KEY MESSAGES: Elevated CRP levels are associated with a shorter overall survival in CLL. Elevated CRP levels are associated with an increased risk of second cancers in CLL. Increased CRP in patients with CLL may justify a more rigorous search for second cancers.